A process-genre approach to teaching argumentative writing to grade nine learners - Elson, Jillian Margaret (Rhodes University, Faculty of Education, Department of Education, 2012)
This action research study aimed to improve teaching and learning of argumentative writing through a process-genre approach. Learners were carefully guided through the processes of writing the argumentative genre, with the focus being on teaching of the genre and on the structural conventions of writing arguments. Participants were a class of grade nine learners who speak English as a first language. They were chosen for this study as Grade Nine is a crucial year for writing development before learners enter the senior phase and are met with heightened expectations in the curriculum, that often they struggle to meet, as their writing has not been sufficiently developed to an academic level. The focus of writing in Grade Nine is on narrative and prose, so this writing intervention, in which a teaching module was developed in collaboration with the 1eamers, aimed to broaden their writing skills and provide them with a head start in leaming the fine art of argumentation, as this is a useful skill to acquire for purposes even beyond the classroom. Genre theorists advocate the importance of teaching genres to leamers at a young age, as it allows them access into different communities of discourse, as they become aware and understand the conventions held by a patiicular community, and realize the purpose of different styles of writing for effectively communicating, which prepares them to meet the expectations of their audience. Teaching the structures of different genres therefore allows the writer, and the audience, a framework for understanding the text. The process approach has been widely used by educators as it focuses on explicit teaching of writing processes that are fundamental to leamers' development in writing. Learners need to be carefully guided from the initial stages, to the more complex stages (especially in argumentative writing which has been deemed the most complex genre for learners to master) in order to understand the complexities of constructing an essay in a cohesive way, as they need to consider multiple aspects of writing, such as the linguistic features, rhetorical features and structural features of the genre and unify them into a sound argument. This takes time, practice and revision, and extensive feedback is required. The process-genre approach proved to be successful in this study, as leamers showed remarkable improvements in their writing from the initial stages of writing to the final drafts of their essays. The findings revealed that explicit teaching of genres and structural elements of writing is vital for ensuring learners' development. Learners require modelling of the genre, scaffolding and careful guidance through step-by-step processes in order to build confidence and express their ideas effectively in written text. The findings indicate the relevance of using the process-genre approach for teaching and learning and that teaching and learning writing is indeed a process that needs more time and practice that is cUiTently allocated in the curriculum.
Keywords: English language -- Rhetoric -- Study and teaching (Secondary); English language -- Writing -- Study and teaching (Secondary); Written communication